Decarbonization of China's transportation sector: In light of national mitigation toward the Paris Agreement goals. (15th July 2018) - Pan, Xunzhang; Wang, Hailin; Wang, Lining; Chen, Wenying
Abstract: Transportation plays an important role in achieving deep decarbonization. This paper examines how the sector might be decarbonized in China in light of three national decarbonization scenarios toward the Paris Agreement goals, using Global Change Assessment Model 4.0 (the Tsinghua University version), which includes a detailed representation of China's transportation. Results indicate that while barely affected by meeting the Nationally Determined Contribution, China's transportation sector might need significant changes beyond 2030 to decouple associated CO2 emissions from GDP growths. Supporting national mitigation has more pronounced implications on freight than passenger transport services, and arouses a radical shift of transport fuels away from fossil-based liquids to clean alternatives. Decarbonizing China's transportation toward 1.5 °C is in many aspects similar to toward 2 °C, but lowers final energy use and ramps up clean fuels at an observably higher pace. In our 1.5 °C scenario, oil-refined liquids tend to phase out in the second half of the century, whereas clean fuels provide 62% (18–36% in 2 °C scenarios) and 98% (68–91% in 2 °C scenarios) of China's transport energy by 2050 and 2100, respectively. Fuel carbon intensity improvements are responsible for the majority of China's transport mitigation in our decarbonization scenarios, followed by energy intensity improvements and transport service reductions. Highlights: China's transportation decarbonization toward the Paris Agreement goals is examined in a bottom-up model. A detailed representation of China's transportation sector is considered. Mitigation scenarios, incorporating China's NDC, are presented toward both 2 °C and 1.5 °C. Dynamics of transport services, modal shifts, energy consumption and CO2 emissions are analyzed toward 2100. The 1.5 °C scenario tends to phase out oil-refined liquids in the second half of the century.